Pengaruh Komunikasi Organisasi Terhadap Motivasi Kerja Karyawan PT Marga Agung Tahun 2022 - Chandra Rio Himawan Chandra; Eldhea Verenisa Kristy; Annisa Farida Hasibuan; Naela Faza Fariha; M. Nastain M. Nastain (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Organizational communication is an important part of an organization to influence one another to achieve an effective quality of organizational communication. Organizational communication also encourages good relationships and coordination of good organization members. The study aims to see how organizational communications can affect the increased motivation for employees' work at the PT Marga Agung Yogyakarta in 2022. This study uses a quantitative methods and a simple regression analysis approach with a linear relationship between variables. Data retrieval was carried out by spreading through Google Forms and direct observation. The method of sampling in this study uses the probability sample and the method using the simple random sampling technique, with the sample data of 113 respondents. The result of this study indicated that oeganizational communication has an effect of 42% on woek motivation and 58% is influenced by variable hat are not measuredor examinedin the process of the result. and states organizational communication has an influenced on work motivation of employes PT Marga Agung Yogyakarta in 2022 with a positive relationship.